2012
DOI: 10.4038/tare.v14i1.4834
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Morphology and Yield Characteristics of Pumpkin (Cucurbita moschata) Genotypes in Northern Bangladesh

Abstract: Twenty pumpkin (Cucurbita moschata) genotypes were characterized for morphological and yield attributes in northern area of Bangladesh during kharif season of 2006. The range of first flowering was at 52.0-73.7 days. The early flowering and early maturity was observed in BD-227 genotype. The range of variability was distinct for vine length at harvest, leaf length, leaf diameter, number of branches per plant. The vine length was maximum (400cm) in BD-242 and minimum (169cm) in BD-255. Leaf length ranged from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 4 publications
3
17
0
2
Order By: Relevance
“…These results are in agreement with the onesreported by , Balkaya et al (2010), Xiaohua et al (2011) and Ahamed et al (2011). Principal Component Analysis (PCA) showed that the three most informative principal components explained 52.5 % of the total variation.The first component accounted for 22.41% of the total variation, and is mainly defined, positively,by skin thickness and seed weight and negatively by seed margin, coat colourand predominant seed coat colour.…”
Section: Resultssupporting
confidence: 83%
“…These results are in agreement with the onesreported by , Balkaya et al (2010), Xiaohua et al (2011) and Ahamed et al (2011). Principal Component Analysis (PCA) showed that the three most informative principal components explained 52.5 % of the total variation.The first component accounted for 22.41% of the total variation, and is mainly defined, positively,by skin thickness and seed weight and negatively by seed margin, coat colourand predominant seed coat colour.…”
Section: Resultssupporting
confidence: 83%
“…Countries such as Bangladesh [15], Egypt [1], Nigeria [10], and Turkey [9,16], have different numbers of Cucurbita species accessions. However, in South Africa the Agricultural Research Council genebank in Roodeplaat, has a total of 36 C. pepo and C. maxima accessions that were only collected from Bushbuckridge, Polokwane and Ladysmith areas [13].…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of fruits per plant was observed in PK09 (7.58) while the lowest number of fruits per plant was found in PK14 (2.96) closely followed by the other inbreds except PK01 (5.38), PK02 (5.13), PK09 (7.58) and PK16 (5.13). Ahmed et al (2011) reported significant differences in fruit per plant in different pumpkin genotypes and the highest number of fruits per plant (15.74) was observed in one genotype. Akter et al (2013) found fruits per plant ranging from 1.52 to 4.60.…”
Section: Number Of Fruits Per Plantmentioning
confidence: 99%
“…Fruit weight differed from one another might be due to inherent character of the inbreds. Ahmed et al (2011) reported significant variation present in average fruit weight and it ranged from 1.51 to 4.20 kg. Pandey et al (2003) obtained that the average fruit weight of pumpkin in the range of 1.33 to 9.10 kg.…”
Section: Average Fruit Weight (Kg)mentioning
confidence: 99%
See 1 more Smart Citation